Reachable workspace and performance of upper limb (PUL) in duchenne muscular dystrophy. Issue 4 (29th December 2015) - Han, Jay J.; de Bie, Evan; Nicorici, Alina; Abresch, Richard T.; Anthonisen, Colleen; Bajcsy, Ruzena; Kurillo, Gregorij; Mcdonald, Craig M.
ABSTRACT: Introduction : The Kinect‐based reachable workspace relative surface area (RSA) is compared with the performance of upper limb (PUL) assessment in Duchenne muscular dystrophy (DMD). Methods : 29 individuals with DMD (ages: 7–23; Brooke: 1–5) underwent both Kinect‐based reachable workspace RSA and PUL assessments. RSAs were also collected from 24 age‐matched controls. Total and quadrant RSAs were compared with the PUL total, shoulder‐, middle‐, and distal‐dimension scores. Results : The total reachable workspace RSA correlated well with the total PUL score (Spearman ρ = ‐0.602; P < 0.001), and with each of the PUL dimensional scores: shoulder (ρ = ‐0.624; P < 0.001), middle (ρ = ‐0.564; P = 0.001), and distal (ρ = ‐0.630; P < 0.001). With quadrant RSA, reachability in a particular quadrant was closely associated with respective PUL dimensional‐level function (lateral‐upper quadrant for shoulder‐, lateral‐upper/lower quadrants for middle‐, and lateral‐lower quadrant for distal‐level function). Conclusions : This study demonstrates concurrent validity of the reachable workspace outcome measure (RSA) with the DMD‐specific upper extremity outcome measure (PUL). Muscle Nerve 53: 545–554, 2016